2007
DOI: 10.1021/jm070104l
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Alogliptin:  A Potent, Selective, Bioavailable, and Efficacious Inhibitor of Dipeptidyl Peptidase IV

Abstract: Alogliptin is a potent, selective inhibitor of the serine protease dipeptidyl peptidase IV (DPP-4). Herein, we describe the structure-based design and optimization of alogliptin and related quinazolinone-based DPP-4 inhibitors. Following an oral dose, these noncovalent inhibitors provide sustained reduction of plasma DPP-4 activity and a lowering of blood glucose in animal models of diabetes. Alogliptin is currently undergoing phase III trials in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(137 citation statements)
references
References 14 publications
3
133
0
1
Order By: Relevance
“…Studies in an opossum kidney proximal tubule cell line indicate that the enzymatic activity of DPP-4 in the proximal tubular brush border may locally affect the generation or breakdown of endogenous factors that regulate Na ϩ reabsorption via effects on NHE3 activity (17). We tested the renal effects of alogliptin (ALG), a novel, high-affinity, high-specificity DDP-4 inhibitor, in the mouse (5,7,13). We hypothesized that the natriuretic effect of ALG involves inhibition of the breakdown of GLP-1 and, thus, depends on an intact GLP-1R.…”
mentioning
confidence: 99%
“…Studies in an opossum kidney proximal tubule cell line indicate that the enzymatic activity of DPP-4 in the proximal tubular brush border may locally affect the generation or breakdown of endogenous factors that regulate Na ϩ reabsorption via effects on NHE3 activity (17). We tested the renal effects of alogliptin (ALG), a novel, high-affinity, high-specificity DDP-4 inhibitor, in the mouse (5,7,13). We hypothesized that the natriuretic effect of ALG involves inhibition of the breakdown of GLP-1 and, thus, depends on an intact GLP-1R.…”
mentioning
confidence: 99%
“…Alogliptin is a potent, selective, bioavailable and efficacious inhibitor of DPP-4 15) . It improves the glycemic control as well as β-cell function, and is well tolerated in type 2 diabetic patients 16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, DPP-4 inhibitors also reportedly inhibit atherosclerosis and inflammation in both GLP-1-dependent and -independent manners 14) . Alogliptin is a potent, selective, efficacious and bioavailable inhibitor of DPP-4 15) . Clinical trials have shown that alogliptin improves the glycemic control, as well as β-cell function, and is well tolerated in type (group C) using drugs other than the DPP-4 inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Wistar fatty rats have been used as a good model for evaluation of a number of anti-diabetic drugs, including a biguanide [84], an -glucosidase inhibitor [75], a thiazolidinedione [85], and an DPPIV-i [86].…”
Section: Drug Treatment and Diabetic Complicationsmentioning
confidence: 99%